Penatalaksanaan Fisioterapi Pada Kondisi Low Back Pain Myogenic Dengan Modalitas Micro Wave Diathermy (Mwd) Dan Core Stability Exercise - Prasetyo, Eko Budi; Permata Kusumawati, Adinda Wira; Alfindana, Dicky (LPPM Universitas Pekalongan, 2024)
Low Back Pain Myogenic is related to disorders of the muscles in the lower back, tendons, and ligaments that can arise when carrying out excessive daily activities such as sitting for long, standing for a long time or lifting weights in the wrong position, where the pain is dull and does not radiate to the chest. limbs. Problematic Low Back Pain Myogenic is pain, spasms, limited range of motion, muscle weakness and decreased functional activity. In this case, the technology chosen is Micro Wave Diathermy (MWD) and Core Stability Exercise.The purpose of the study was to determine the effect of physiotherapy management on Low Back Pain Myogenic conditions with Micro Wave Diatermy (MWD)and Core Stability Exercise as modalities. The research design used in this research is descriptive analytic method. The subjects of this study were patients at Kajen Hospital, Pekalongan Regency. The method of data collection was the analysis of this research data using the autoanamnesis method. The results of the study as many as 5 treatments were as follows: (1) there was a decrease in T1:4 to T5:2 motion pain (2) there was a decrease in spasm from T1:1 to T5:0 (3) there was an increase in ROM in all Trunk movements (4) there is an increase in muscle strength from T1:3 to 4 (5) there is an increase in daily functional activities. The conclusion of the study is that physiotherapy interventions with Micro Wave Diathermy (MWD) and Core Stability Exercise modalities can reduce problems that arise in the Myogenic Low Back Pain condition.Keywords: Micro Wave Diathermy (MWD) and Core Stability Exercise